Settling behaviors of microplastic disks in water. (March 2023) - Yang, Ge; Yu, Zijian; Baki, Abul B.M.; Yao, Weiwei; Ross, Matthew; Chi, Wanqing; Zhang, Wenming
Abstract: Microplastic (MP) disks have not been studied for settling behaviors in aquatic environments, which affects the transport and fate of MPs. Therefore, settling experiments were conducted on MP disks of three shapes and four common-seen materials. Lighter MP disks (with density ρ s = 1.038 g/cm 3 and length l ≤ 5 mm) followed rectilinear vertical trajectories, while heavier MP disks ( ρ s = 1.161–1.343 g/cm 3 and l = 5 mm) followed zigzag trajectories with oscillations and rotations. The mean terminal settling velocities of MP disks were 19.6–48.8 mm/s. Instantaneous settling velocities of heavier MP disks fluctuated. Existing formulas could not accurately predict the settling velocity of MP disks; thus, a new model was proposed with an error of 15.5 %. Finally, the Re d - I* diagram ( Re d is the disk Reynolds number and I* is the dimensionless moment of inertia) was extended for MP disks to predict settling trajectories. Highlights: MP disks show linear or zigzag settling trajectory, depending mainly on density. A new model was proposed for predicting the mean settling velocity of MP disks. Instantaneous settling velocities and trajectoreis of MP disks were examined. The Re d - I* diagram was extended for MP disks to predict settling trajectories.